Acute Kidney Injury in 43 Years Old Male Patient Caused by Severe Leptospirosis - Ajeng Sulistianing Utami; Amanukarti Resi Oetomo (Lombok Medical Journal, 2026)
Leptospirosis is a zoonotic infectious disease commonly found in tropical regions, caused by Leptospira interrogans, a pathogenic spirochete. The main reservoir is rodents, especially rats. Human transmission occurs either directly through inoculation from infected animal tissues, body fluids and urine, or indirectly through contact via mucosal surfaces or abraded skin. The excretion of organisms through the urine of infected animals represents the most common source of Leptospira infection. As of mid-2024, 367 cases of leptospirosis with 42 deaths had been reported in Indonesia. However, the true incidence is likely underreported due to diagnostic challenges. In West Nusa Tenggara (NTB), no formal report exists; however, a data from Mataram City Hospital between 2013-2025 recorded three cases of leptospirosis involving renal impairment requiring hemodialysis (HD). The clinical course of leptospirosis is typically acute, following an incubation period of five to fourteen days. Most patients present with mild, anicteric febrile, but a smaller subset develop severe multiorgan involvement known as Weil’s Disease. The severe form is characterized by acute high-grade fever, acute kidney injury, hepatic failure, pulmonary involvement, cardiovascular instability, neurological deficits, and hemorrhagic diathesis.